A CLINICAL STUDY ON THE EFFICACY OF VASA PRATISARANEEYA TEEKSHNA KSHARA IN THE MANAGEMENT OF ABHAYANTARA ARSHA/HAEMORRHOID - Himadri Mudgal; P. Hemantha Kumar (International Journal of Ayurveda and Pharma Research, 2020)
Astamahagda, group of eight dreadful clinical conditions told in all Ayurvedic classics. Aacharya Sushruta enlisted Arsha in Astamahagada. Arsha is known as haemorrhoids in modern parlance. The altered lifestyle in this modern world is the leading cause in the incidence of Haemorrhoids (Arshas). Symptoms of internal haemorrhoids closely resemble to clinical features of Abhyantara Arshas. Aacharya Shusruta described four types of treatment modalities for the management of Arsha, they are Bheshaja Karma, Kshara Karma, Agni Karma and Shastra Karma. Kshara is one of the most essential methods that can be used safely. An attempt has been made in this study to test the effectiveness of Vasa Pratisaraneeya Teekshna Kshara in the management of Abhayantra Arsha. In this study, 15 patients suffering from Abhyantra Arsha were selected from OPD and IPD of the PG Department of Shalya Tantra, NIA, Jaipur. The data obtained have been statistically analyzed and it has been observed that Kshara Karma is effective in curing the disease, preventing recurrence and cost-effective Para-surgical procedure. The outcome of Kshara Karma interference is motivating.